Actual problems of religious studies specialists training in the conditions of modern Kazakhstan - Байтенова, Нагима (Eurasian Journal of Religious Studies, 2017)
For modern Kazakhstan in one of the most pressing problems is the problem of training of specialists in the field of religious studies. The article describes the history of achievements in the training of specialists in the field of religious studies after Kazakhstan became independent, provided a comprehensive analysis of the problems of education and training, issues of religious education and religious studies, also discussed issues related to religious and theological illiteracy. Also in the article is given enough attention to the processes and trends of the future training of specialists in areas of religious studies and Islamic studies.